A resident-led initiative to improve patient safety event reporting in an internal medicine residency program - Kevin Zarrabi; Kelly Cummings; Nicole Lum; Erin Taub; Nirvani Goolsarran (Greater Baltimore Medical Center, 2020)
Background Despite the Clinical Learning Environment Review's recommendations of their use, patient safety event reporting systems are underutilized by residents. Objective We aimed to identify perceived barriers to event reporting amongst internal medicine residents and implement a targeted quality improvement initiative to address the identified barriers and increase overall resident event report rates. Methods A total of 94 Internal Medicine (IM) residents participated in the educational intervention in 2018. We measured residents' perception of barriers to event reporting and employed the results of the questionnaire to create a skill-based educational workshop. We conducted the plan-do-study-act model to test a structured educational intervention and its effectiveness on pre-post IM residents' event report rates and compared it to report rates of Non-Internal Medicine (Non-IM) residents. Additionally, we assessed pre-post intervention knowledge, skills, and attitudes in event reporting. Results 94/94 (100%) of IM residents had a significantly higher median percent of patient safety event reporting when compared to pre-intervention (23.6% compared to 5.88%, p-value = 0.0030) and when compared to Non-IM residents (23.6% compared to 5.31%, p-value = 0.0002). Residents performed better on the post-test compared to the pre-test (90% compared to 30%, p-value = 0.0001) for knowledge. 100% of the critical action items were completed and 90% of participants reported their perception of the event reporting process improved. Conclusions By elucidating common reasons why residents are not reporting patient safety events, a specific intervention can be created to target the identified impediments and improve resident event reporting. Abbreviations IM: Internal Medicine IM; Non-IM: Non-Internal Medicine; IOM: Institute of Medicine I; ACGME CLER: Accreditation Council for Graduate Medical Education Clinical Learning Environment Review; GME: Graduate Medical Education; IRB: Institutional Review Board; PDSA: Plan, Do, Study, Act